Risk Management Practices and Profitability of Microfinance Banks in Rwanda A Case of Urwego Bank - Gahongayire, Lydia; Kamande, Mercyline (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
Financial institutions are major players in the economic development of a country by offering channels through which funds flow from one source to another. However, they are faced with numerous risks in their daily operations. The main goal behind the current research was to assess the effect of risk management practices on the profitability of microfinance banks in Rwanda, a case of Urwego Bank. Both descriptive and correlational research designs were used. Data was collected from the targeted population of 113 employees in Urwego Bank who were considered for the sampling using the census method. The data was collected using structured questionnaire and interview guide for key informants. The research instrument reliability test was done using Cronbach’s alpha test while the validity was achieved through revision of the questionnaire after a pre-test is conducted. The data that collected was analyzed using SPSS through which data was presented using frequency tables, descriptive statistics, and regression analysis. The findings on risk assessment revealed that 77.8% of the respondents agreed that they can conduct risk identification. A total of 63.4% of the respondents agreed on the importance of risk classification. The regression analysis revealed that there is combined effect of risk measurement, risk identification and risk classification on the profitability of the bank giving an R2 of 0.418. On whether having control measures within a bank can greatly assist in effective risk management, 82.5% of the respondents agreed. 73% of the respondents agreed that risk mitigation strategies are effective ways of reducing the possibility of occurrence of risk and their impact in an organization. 74.1% of respondents showed that risk financing is important for the Bank in its management of risk. Further, regression analysis showed the model was fit at 5% and an R2=0.582 indicating that the changes in profitability of the Bank are influenced by risk control measures. The regression model regarding the risk monitoring was found to be significant and an showing that the profitability in Urwego Bank is influenced by risk monitoring processes. The overall regression model was significant and an R2=0.536 and showed that risk management practices should be practiced in totality to ensure that effective results are obtained. Therefore, the researcher recommended that policy makers and supervisors, including the central bank, should be more vigilant in promulgating the culture of risk management in the banks especially for microfinance banks which are few in the industry.